Building Vue.js Applications with GraphQL: Develop a complete full-stack chat app from scratch using Vue.js, Quasar Framework, and AWS Amplify - Ribeiro, Heitor Ramon (Packt Publishing, 2021)
Take your Vue.js knowledge to the next level by understanding full-stack development concepts and exploring modern web technologies such as AWS Amplify, GraphQL, and Quasar Framework Key Features Build a fully functional Vue.js web app and learn how it integrates with GraphQLTransform your chat application into a Progressive Web Application (PWA) for web deploymentDiscover practical recipes, exploring the capabilities of the GraphQL API for full-stack development using Quasar Framework Book Description Since its release by Facebook in 2012, GraphQL has taken the internet by storm. Huge companies such as Airbnb and Audi have started to adopt it, while small to medium-sized companies are now recognizing the potential of this query-based API. GraphQL may seem strange at first, but as you start to read about and experience more of it, you won’t want to use REST APIs anymore. With the recipes in this book, you will learn how to build a complete real-time chat app from scratch. Starting by creating an AWS Amplify environment, you will delve into developing your first GraphQL Schema. You will then learn how to add the AppSync GraphQL client and create your first GraphQL mutation. The book also helps you to discover the simplicity and data fetching capabilities of GraphQL that make it easy for front-end developers to communicate with the server. You will later understand how to use Quasar Framework to create application components and layouts. Finally, you will find out how to create Vuex modules in your application to manage the app state, fetch data using the GraphQL client, and deploy your application to the web. By the end of this book, you’ll be well versed in proof-of-concept full-stack applications that explore the power of GraphQL with AWS Amplify, and you'll be able to use Quasar Framework to create your Vue applications. What you will learn Set up your Vue.js projects with Vue CLI and explore the power of Vue componentsDiscover steps to create functional components in Vue.js for faster renderingBecome familiar with AWS Amplify and learn how to set up your environmentUnderstand how to create your first GraphQL schemaUse Quasar Framework to create simple and effective interfacesDiscover effective techniques to create queries for interacting with dataExplore Vuex for adding state management capabilities to your appDiscover techniques to deploy your applications effectively to the web Who this book is for This book is for intermediate-level Vue.js developers who want to take their first step toward full-stack development. Prior knowledge of Vue.js and JavaScript is required before getting started with this book.